Endocrine involvement in mitochondrial encephalomyopathy with partial cytochrome c oxidase deficiency. Issue 1 (January 1989) - Doriguzzi, C; Palmucci, L; Mongini, T; Bresolin, N; Bet, L; Comi, G; Lala, R
Abstract : A 19-year-old man born with thyroprivic hypothyroidism, due to congenital development defect, manifested hypogonadism, stunted growth, chronic progressive external ophthalmoplegia (CPEO), diffuse muscle weakness and wasting, right bundle branch block, cerebral atrophy. Muscle biopsy showed mitochondrial abnormalities. Biochemical investigations on muscle disclosed partial (50%) cytochrome c oxidase deficiency, 58% decrease of cytochrome aa3 and 41% decrease of cytochrome b. Enzyme-linked immunosorbent assay showed decrease of the immunologically active enzyme protein.